Optimization of Human Resources in the Construction Industry at PT. Superior Pusadega - Yusana, Yeva; Helmi, Sulaiman; Isnawijayani; Trisninawati (Sinergi International Journal of Management and Business, 2024)
This research discusses efforts to optimize human resources (HR) in the construction industry at PT. Pusadega Superior. Effective HR management is crucial for increasing productivity and reducing risks in construction projects. The main problem identified is how HR optimization strategies influence project performance and job satisfaction. This study offers a new perspective by analyzing a comprehensive approach to HR management in the construction sector, an area that has not been widely explored in previous research. The research employs a qualitative case study method, utilizing qualitative analysis through interviews with project managers and staff, as well as document review related to HR management at PT. Pusadega Superior. The findings reveal that despite having good HR policies, their implementation is often inconsistent, which negatively impacts project performance. The main influencing factors are the quality of training and internal communication. The conclusion of this research is that increasing consistency in the implementation of HR policies and improving training and communication can enhance project performance and job satisfaction. The implication is that PT. Pusadega Superior must invest in better training programs and more effective communication strategies. The key message is that effective HR optimization is critical to the success of construction projects and worker satisfaction.